Concise Review: Stem Cell Interventions for People With Cerebral Palsy: Systematic Review With Meta‐Analysis. (31st May 2016) - Novak, Iona; Walker, Karen; Hunt, Rod W.; Wallace, Euan M.; Fahey, Michael; Badawi, Nadia
Abstract : This study examines stem cells as a potential intervention for people with cerebral palsy. Results show that stem cells appear to induce short‐term improvements in motor skills. Abstract : Evidence for stem cells as a potential intervention for cerebral palsy is emerging. Our objective was to determine the efficacy and safety of stem cells for improving motor and cognitive function of people with cerebral palsy. Searches were conducted in October 2015 in CENTRAL, EMBASE, MEDLINE, and Cochrane Libraries. Randomized controlled trials and controlled clinical trials of stem cells for cerebral palsy were included. Two authors independently decided upon included trials, extracted data, quality, and risk of bias. The primary outcome was gross motor function. Secondary outcomes were cognitive function and adverse events (AEs). Effects were expressed as standardized mean differences (SMD) with 95% confidence intervals (CI), using a random‐effects model. Five trials comprising 328 participants met inclusion criteria. Four cell types were studied: olfactory ensheathing, neural, neural progenitors, and allogeneic umbilical cord blood (UCBs). Transplantation procedures differed from central nervous system neurosurgical transplantation to intravenous/arterial infusion. Participants were followed short‐term for only 6 months. Evidence of variable quality indicated a small statistically significant intervention effect from stem cells on gross motor skills (SMD 1.27; 95% CI 0.22, 2.33), with UCBs most effective. There were insufficient and heterogeneous data to compare cognitive effects. Serious AEs were rare ( n = 4/135 [3%] stem cells; n = 3/139 [2%] controls). Stem cells appeared to induce short‐term improvements in motor skills. Different types of stem cell interventions were compared, meaning the data were heterogeneous and are a study limitation. Further randomized controlled trials are warranted, using rigorous methodologies. Significance: Stem cells are emerging as a scientifically plausible treatment and possible cure for cerebral palsy, but are not yet proven. The lack of valid animal models has significantly hampered the scope of clinical trials. Despite the state of current treatment evidence, parents remain optimistic about the potential improvements from stem cell intervention and feel compelled to exhaust all therapeutic options, including stem cell tourism. Receiving unproven therapies from unvalidated sources is potentially dangerous. Thus it is essential that researchers and clinicians stay up to date. A systematic review and meta‐analysis summarizing and aggregating current research data may provide more conclusive evidence to inform treatment decision making and help direct future research.